REAKTUALISASI EPISTEMOLOGIS ISLAM: IMPLIKASINYA TERHADAP PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM DI ERA SOCIETY 5.0 - Isnaini; Jundan Niswa Khoirunnisa; Muhammad In’am Esha; Imron Rossidy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The transformation toward the Society 5.0 era demands a reconstruction of the epistemological framework in Islamic education so that it can respond to the integration of humans, technology, and human values in a balanced manner. This article aims to analyze the reactualization of Islamic epistemology and its implications for the development of an adaptive, integrative, and contextual Islamic education curriculum. The approach used is a qualitative one based on Library Research, involving a critical analysis of classical and contemporary sources in Islamic epistemology as well as modern educational literature. The results of the study indicate that: (1) The re-actualization of Islamic epistemology is grounded in revelation, reason, and empirical experience. (2) Its implications for the development of an Islamic education curriculum for Society 5.0 include the development of curriculum objectives, content, learning approach strategies, and an Islamic education curriculum evaluation system.